Effect of Assertiveness Training Methods on Social Adjustment - Eshagh Rahimian Boogar; Hossein Shareh; Mojtaba Habibi Askarabad; Mohamad Alli Besharat (فصلنامه نوآوری‌های آموزشی, 2007)
The aim of this study was to determine and compare the efficacy of assertiveness training Methods (assertive refusal, assertive expression and assertive commentary) on social adjustment of boy and girl students of Shahreza Guidance Course in 2005-2006 school year.240 students (120 boy students and 120 girl students) of third grade in middle school (Grade 8) were selected using stratified random selection from students of Shahreza Guidance Course as the subjects of the research. They were randomly assigned into experimental groups and a control group. Prior to the educational intervention, experimental groups and a control group were assessed by Vinelend Adaptive Behavior Scales. Only the subjects in experimental groups were exposed to 10 sessions of assertiveness training in group manner. The subjects in the control group received no interventions. Upon completion of the intervention, experimental groups and a control group were assessed once again by the aforementioned test. Data were analyzed and interpreted by covariance analysis, pair-wise comparisons (Bonferoni). Research findings showed that significant difference existed in group membership variable in comparison between experimental groups and a control group. Significant difference existed in comparing social adjustment between boy and girl students. Also, analysis of interaction between group and sex variables showed that significantly difference existed. Also, analysis of multiple comparisons of Bonferoni implied that significantly difference exists between comparisons of experimental groups with control group. The results point to the fact that assertiveness training methods including assertive refusal, assertive expression, and assertive commentary are effective in modifying the social adjustment and assertiveness training methods. These can be considered a primary and fundamental need in educational backgrounds.